Relationships among pest flour beetles of the genus Tribolium (Tenebrionidae) inferred from multiple molecular markers - Angelini, David R. (2007)
Model species often provide initial hypotheses and tools for studies of development, genetics, and molecular evolution in closely related species. Flour beetles of the genus Tribolium MacLeay (1825) are one group with potential for such comparative studies. Tribolium castaneum (Herbst 1797) is an increasingly useful developmental genetic system. The convenience with which congeneric and other species of tenebrionid flour beetles can be reared in the laboratory makes this group attractive for comparative studies on a small phylogenetic scale. Here we present the results of phylogenetic analyses of relationships among the major pest species of Tribolium based on two mitochondrial and three nuclear markers (cytochrome oxidase 1, 16S ribosomal DNA, wingless, 28S ribosomal DNA, histone H3). The utility of partitioning the dataset in a manner informed by biological structure and function is demonstrated by comparing various partitioning strategies. In parsimony and partitioned Bayesian analyses of the combined dataset, the castaneum and confusum species groups are supported as monophyletic and as each other’s closest relatives. However, a sister group relationship between this clade and Tribolium brevicornis (Leconte 1859) is not supported. Therefore, we suggest transferring brevicornis group species to the genus Aphanotus Leconte (1862). The inferred phylogeny provides an evolutionary framework for comparative studies using flour beetles.